SOME REFLECTIONS ON THE STRUCTURAL LINGUISTICS APPLIED TO THE NOMINAL SENTENCE IN ARABIC - Luisa Maria Arvide Cambra (European Scientific Journal, ESJ, 2015)
The article analyzes the diverse results obtained in the syntactic analysis of the nominal sentence in Arabic according to the methods of structural linguistics from two different perspectives: the Arab way and the European-American way. By using the technique of the contrastive analysis, the study provides interesting data about the similarities and the differences between Arabic and English in relation to the nominal sentence when the morphosyntactic principles of structural linguistics are applied.